Request Strategies in Kuwaiti Arabic and British English: A Cross-Cultural Pragmatic Study - Yasmeen B AlMujaibel; Yasser A. Gomaa (RIRAI Publisher, 2022)
The study at hands is a cross-cultural exploration of request strategies in Kuwaiti Arabic and British English dialects. A mixed method approach of a qualitative and quantitative analysis was used (i.e., a Discourse Completion Test (DCT) and semi-structured interviews). Data was collected from a total of five hundred participants, two hundred and fifty from each group. Sixty participants were chosen for the semi-structured interviews. The analysis of the collected data was based upon Brown and Levinson's (1987) social variables (e.g., power, distance, and ranking). Also, the data was analyzed following Blum-Kulka and Olshtain's (1984) Cross-Cultural Speech Act Realization Project (CCSARP). The results of the study revealed that Kuwaiti Arabic and British English participants used the conventional indirect level in the form of query preparatory in most situations. Furthermore, power as a social variable affected Kuwaiti Arabic and British English participants’ flow of a request in conversations. Participants used direct request strategies when the power of the speaker was high. As for the semi-structured interviews, the results indicated that there is a sociocultural norm between the Kuwaiti society and the British society, which affected their use of requests.